Young athletes' motivational profiles - Moreno Murcia, J. A.; Cervello Gimeno, E.; Gonzalez-Cutre, D. (Journal of Sports Science & Medicine, 2007)
The aim of this study was to examine the relationship between motivational characteristics and dispositional flow. In order to accomplish this goal, motivational profiles emerging from key constructs within Achievement Goal Theory and Self-Determination Theory were related to the dispositional flow measures. A sample of 413 young athletes (Age range 12 to 16 years) completed the PMCSQ-2, POSQ, SMS and DFS measures. Cluster analysis results revealed three profiles: a "self-determined profile" characterised by higher scores on the task-involving climate perception and on the task orientation; a "non-self-determined profile", characterised by higher scores on ego-involving climate perception and ego orientation; and a "low self-determined and low non-self-determined profile" which had the lowest dispositional flow. No meaningful differences were found between the "self-determined profile" and the "non-self-determined profile" in dispositional flow. The "self-determined profile" was more commonly associated with females, athletes practising individual sports and those training more than three days a week. The "non-self-determined profile" was more customary of males and athletes practising team sports as well as those training just two or three days a week.